Spontaneous tumor regression following COVID-19 vaccination - Hui Dai; Renata Ferrarotto; Myrna Godoy; Diana Bell; Shiaw-Yih Lin; Daniel J McGrail; Luana Guimaraes de Sousa; Kaiyi Li; Mario L Marques-Piubelli; Cipriano Gonzalez; Sammy Ferri-Borgogno; Jared Burks (Journal for ImmunoTherapy of Cancer)
Vaccination against COVID-19 is critical for immuno-compromised individuals, including patients with cancer. Systemic reactogenicity, a manifestation of the innate immune response to vaccines, occurs in up to 69% of patients following vaccination with RNA-based COVID-19 vaccines. Tumor regression can occur following an intense immune-inflammatory response and novel strategies to treat cancer rely on manipulating the host immune system. Here, we report spontaneous regression of metastatic salivary gland myoepithelial carcinoma in a patient who experienced grade 3 systemic reactogenicity, following vaccination with the mRNA-1273 COVID-19 vaccine. Histological and immunophenotypic inspection of the postvaccination lung biopsy specimens showed a massive inflammatory infiltrate with scant embedded tumor clusters (<5%). Highly multiplexed imaging mass cytometry showed that the postvaccination lung metastasis samples had remarkable immune cell infiltration, including CD4+ T cells, CD8+ T cells, natural killer cells, B cells, and dendritic cells, which contrasted with very low levels of these cells in the prevaccination primary tumor and lung metastasis samples. CT scans obtained 3, 6, and 9 months after the second vaccine dose demonstrated persistent tumor shrinkage (50%, 67%, and 73% reduction, respectively), suggesting that vaccination stimulated anticancer immunity. Insight: This case suggests that the mRNA-1273 COVID-19 vaccine stimulated anticancer immunity and tumor regression.